An efficient dynamic volume rendering for large-scale meteorological data in a virtual globe. (May 2019) - Zhang, Xuequan; Yue, Peng; Chen, Yumin; Hu, Lei
Abstract: Texture slicing based volume rendering is widely used for data visualization, but dynamic high-fidelity rendering for large-scale meteorological data is still a challenge. The traditional octree-based multiresolution method increases the slicing and rendering batches, and it also has the visual defect of brick borders. This paper introduces an efficient dynamic volume rendering method for large-scale meteorological data in a virtual globe. First, the volumetric data is resampled and transformed adaptively according to the camera view. Second, the proxy geometry is calculated by slicing the whole spherical shaped volume along the ray from the camera to Earth center based on GPU. Finally, the rendering efficiency is optimized for interactive dynamic visualization. The proposed method is tested by visualizing Typhoon Rananim in an open source software, called World Wind. The experimental results demonstrate that the proposed method is more efficient and the visual effect is smoother than the octree-based multiresolution method. Highlights: The method can dynamically visualize large-scale meteorological volume data. A pyramid data structure for spherical volume is proposed. A rendering strategy slicing whole spherical volume along camera to Earth center. The method has a smooth visual effect. The method realizes dynamic volume rendering above 33 frames per second.